1981
DOI: 10.1159/000299605
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Pressor Response to Angiotensin II during Pregnancy and Nursing in the Rabbit

Abstract: A continuous study to determine blood pressure and pressor response to angiotensin II (A-2) during pregnancy and postpartum was performed in a chronic rabbit preparation. The resting blood pressure during pregnancy was found to be lower than that in the postpartum period. Pressor response to A-2 was diminished during pregnancy and during nursing, but in the absence of nursing, this response returned to normal values by 1 week postpartum. Inhibition of prostaglandin synthetase caused a significant increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Though these groups carried out their experiments on unanaesthetized rabbits whereas those of our study and that of O 'Brien et al (1977) were anaesthetized, this is only one of the factors which may contribute to the divergent findings. Thus Katz and Creasy (1981) found infusion of angiotensin I1 at 50 ng/kg per min raised arterial pressure in their pregnant rabbits by 14 mmHg; this is virtually identical to the rise of 14.9 mmHg found in this study when angiotensin I1 was infused at 54 pmol/kg per min, which is equivalent to 55 ng/kg per min ( Table 3). It is the results from the two laboratories for the non-pregnant animals that appear to conflict.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Though these groups carried out their experiments on unanaesthetized rabbits whereas those of our study and that of O 'Brien et al (1977) were anaesthetized, this is only one of the factors which may contribute to the divergent findings. Thus Katz and Creasy (1981) found infusion of angiotensin I1 at 50 ng/kg per min raised arterial pressure in their pregnant rabbits by 14 mmHg; this is virtually identical to the rise of 14.9 mmHg found in this study when angiotensin I1 was infused at 54 pmol/kg per min, which is equivalent to 55 ng/kg per min ( Table 3). It is the results from the two laboratories for the non-pregnant animals that appear to conflict.…”
Section: Discussionsupporting
confidence: 80%
“…O'Brien et al (1977) injected angiotensin in a range of doses similar to those used in the present study and found the percentage increase in mean arterial pressure to be greater in pregnant rabbits. On the other hand, Berssenbrugge et al (1980), Katz and Creasy (1981) and Lee et al (1982) found a diminished response to angiotensin I1 in pregnant rabbits. Though these groups carried out their experiments on unanaesthetized rabbits whereas those of our study and that of O 'Brien et al (1977) were anaesthetized, this is only one of the factors which may contribute to the divergent findings.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In studies on the effect of exogenous A11 in rabbits (Katz & Creasy 1981) it was shown that the blood pressure response was reduced much to the same extent during lactation and during late pregnancy. Our lactating goats, however, showed a pressor response to A11 similar to, or greater than that during anoestrus.…”
Section: Discussionmentioning
confidence: 97%